Perancangan Lansekap Kawasan Desa Pondok Balik Menuju Desa Wisata Kabupaten Aceh Tengah - Sri Shindi Indira; Rahmadhani Fitri; M. Fajar Lut Tawar (Jurnal Teknik dan Teknologi Indonesia, 2023)
Desa Wisata" translates to "tourist village" in English. It refers to a tourism activity aimed at promoting local tourism by utilizing the cultural, natural, and traditional attractions of the village. "Desa Pondok Balik" is one such village located in the Central Aceh Regency, which has tourism potential in both agriculture and its natural features, particularly a river area known as Sungai Balik situated in the southern part of the village. The landscape design to be carried out will focus on this river area, with the hope that it can support the concept of a Tourist Village in Desa Pondok Balik. The design is guided by the principles of sustainable tourism, aiming to create a tourist area that not only benefits the local economy but also preserves and conserves the environment. Additionally, cultural values, specifically the Gayo culture, are also incorporated into this design concept.